Peramalan Harga Minyak Goreng Pada Masa Pemulihan Pandemi Covid-19 Di Pasar Kabupaten Blitar - Swastika, Galuh Tyasing; Nada, Luthfi Qathrun; Sanwidi, Ardhi (UJMC (Unisda Journal of Mathematics and Computer Science), 2024)
The impact of Covid-19 is still felt on the unstable economic sector in Indonesia, one of which is cooking oil where the price has soared. DISPERINDAG as a service that has duties, one of which is in monitoring and supervising the price of basic necessities, so knowing the prediction of the price of goods can make it easier for DISPERINDAG to carry out its duties in maintaining the stability of the price of basic necessities, especially those in the market. So the author is interested in researching the forecasting of cooking oil prices during this transition period with the single exponential smoothing method. The data used for the study is daily data on the price of cooking oil without brand in the Blitar Regency market for 426 days from August 1, 2021 - September 30, 2022 then the data can to predict the price of cooking oil in October 2022. The results of the study obtained an alpha value of 0.9 to be the smallest error value with an average MAPE of 7.41% and the predicted results of bulk cooking oil prices in the Blitar Regency market in October 2022 of Rp 12929.97/liter.